Geriatric palliative care: clinical imperatives, ethical challenges and public health opportunities (Swiss Medical Weekly, 2026)
Population ageing is accelerating globally, creating complex clinical, ethical and organisational challenges for health systems. Older adults frequently experience multimorbidity, frailty and cognitive impairment, leading to unpredictable illness trajectories and high palliative care needs. Geriatric palliative care (GPC) has emerged as an integrative approach uniting geriatric, palliative and rehabilitative principles to address these multidimensional needs. Recent European recommendations emphasise needs‑based assessment, interdisciplinary collaboration, caregiver support, culturally sensitive communication and integration across care settings. In Switzerland, persistent barriers – including fragmented care pathways, limited workforce training, variable access in nursing homes, low uptake of advance care planning and inequities affecting socioeconomically and culturally diverse populations – underscore the urgency of implementing coordinated GPC models. Strengthening home‑ and nursing home‑based palliative care, embedding GPC competencies in undergraduate and postgraduate curricula, establishing shared‑care frameworks and aligning national strategies with international ageing agendas represent key priorities. Investment in GPC is essential to ensure equitable, person‑centred and sustainable care for a rapidly growing population of frail older adults.